Workflow for Comparison of Chemical and Biological Metrics of Filter Collected PM(2.5) - Roper, Courtney (Atmos Environ (1994), 2020)
There is limited understanding of adverse health effect associations with chemical constituents of fine particulate matter (PM(2.5)) as well as the underlying mechanisms. We outlined a workflow to assess metrics, beyond concentration, using household and personal PM(2.5) filter samples collected in India as a proof of concept for future large-scale studies. Oxidative potential, chemical composition (polycyclic aromatic hydrocarbons and elements), and bioactivity (developmental exposures in zebrafish) were determined. Significant differences were observed in all metrics between personal and household PM(2.5) samples. This work established methods to characterize multiple metrics of PM(2.5) to ultimately support the identification of more health-relevant metrics than concentration.